Possible deconstruction of trauma. A post-modern approach - Cruz Villalobos, Luis (Universidad de Chile. Programa Domeyko, 2012)
Is it possible to look at psychological trauma beyond a perspective that is centered on the irremediable, in the chronic permanence of damage? Can the traumatic be deconstructed?In this article, outlined from a post-modern referential frame, the subject of psychological trauma is presented from a deconstructive angle, connecting it with recent research in the fields of resilience and post-traumatic growth.  These represent examples of new approaches that enable to overcome the effects of extreme adversity, both at a personal and a communitarian level.